Poliklinik Koh Clinic Management System - Nicole Ng Kit Tee,; Munirah Mohd Yusof, (Applied Information Technology And Computer Science, 2023)
The goal of putting in place the Clinic Management System for Poliklinik Koh is to create, build, and test a web-based system for managing the clinic that uses an organised method to give each type of user their own set of functions. A method called "Agile development" was used to make the system that was put in place. The system's technological language is constructed using Visual Studio Code and phpMyAdmin as a MySQL database administration tool. The system has four types of users: the supervisor, the doctor, the clinic staff, and the student. Also, the applied system has five functional parts, such as user management, schedule management, service management, report generation, and job management. The test plan was carried out by the system that was put into place to make sure that the units worked as planned. In short, the method that was put in place makes Poliklinik Koh's operation better and gives people a place to meet their needs.